Re:thinking Europe
1 online resource
Keywords: What is Europe? This question is ever more pressing, as present day Europe wallows in crisis - its deepest since the process of European integration took off in the 1950s. The current state of affairs sets the stage for this book. It brings together leading international thinkers and scholars of different generations in a feverish quest to better understand Europe's present state. In their essays these authors engage in the paradoxes and puzzles of European identity and culture. They present new answers to the eternal question regarding 'the essence of Europe'. An anthology of influential texts from the making of present-day Europe completes the book as a very European exercise in thinking and re-thinking Europa, its culture, history and present.